Thermoplastic resin composition, fiber-reinforced resin substrate and molded article

The thermoplastic resin composition, featuring a thermoplastic resin with an electron-donating group and a transition metal compound, addresses the challenges of thermal stability and mechanical properties in harsh environments, achieving superior performance even after heating.

JP7658088B2Active Publication Date: 2025-04-08TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020549080
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-24
Filing Date
2020-09-11
Publication Date
2025-04-08
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

Existing thermoplastic resin compositions face challenges in maintaining thermal stability and mechanical properties, especially in harsh environments, where they experience significant reduction in tensile elongation at break after heating.

Method used

A thermoplastic resin composition comprising a thermoplastic resin with an electron-donating group and a transition metal compound, specifically a nickel compound and a copper compound with a complete decomposition temperature of 400°C or higher, along with an amine compound, to enhance thermal stability and mechanical properties.

Benefits of technology

The composition achieves excellent thermal stability and mechanical properties, with improved retention of melt viscosity and tensile strength even after heating, effectively addressing the limitations of prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658088000011
    Figure 0007658088000011
  • Figure 0007658088000012
    Figure 0007658088000012
  • Figure 0007658088000013
    Figure 0007658088000013
Patent Text Reader

Abstract

The purpose of the present invention is to provide a thermoplastic resin composition having exceptional thermal stability and mechanical characteristics, a fiber-reinforced resin substrate, and a molded article obtained therefrom. In order to achieve the abovementioned purpose, an embodiment of the present invention has the structure described below. Specifically, a thermoplastic resin composition including a thermoplastic resin (A) having an electron-donating group, and a transition metal compound (B), wherein the transition metal compound (B) includes a nickel compound (B1) and a copper compound (B2), the complete decomposition temperature of the copper compound (B2) is 400°C or higher, and the copper compound (B2) has a nickel content of 0.001-4 parts by mass (inclusive) and a copper content of 0.001-4 parts by mass (inclusive) with respect to 100 parts by mass of the thermoplastic resin (A) having an electron-donating group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition, a fiber-reinforced resin substrate, and a molded article. [Background technology]

[0002] In recent years, the environmental temperature of resins used in automobiles, aircraft, and other applications has risen with the increasing density of parts and increased power output. For this reason, highly heat-resistant resins, such as super engineering plastics, are widely used. Demand for super engineering plastics is expanding in fields with extremely harsh operating conditions and as a metal replacement material, and there is a demand for improved thermal stability and mechanical properties.

[0003] As a means for improving the thermal stability of thermoplastic resins, Patent Document 1 describes that blending a polyphenylene ether resin and a polyamide resin with a metal halide or metal carboxylate of a metal selected from copper, nickel, tin and cerium results in excellent thermal stability.

[0004] Furthermore, as a technique for using a nickel compound and a copper compound in combination with a thermoplastic resin, Patent Document 2 discloses that a thermoplastic resin composition having excellent moldability, designability, scratch resistance, and impact resistance can be obtained by adding at least one additive element selected from cobalt, nickel, copper, and lead to a butadiene resin, and describes in an example the combined use of nickel nitrate and copper nitrate.

[0005] Furthermore, Patent Document 3 discloses that the inclusion of an aromatic amine compound in combination with polyarylene sulfide and polyalkylene glycol results in excellent thermal stability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 1-163262 [Patent Document 2] JP 2014-227367 A [Patent Document 3] Japanese Patent Application Publication No. 6-207102 Summary of the Invention [Problem to be solved by the invention]

[0007] The methods proposed in Patent Documents 1 to 3 provide thermoplastic resin compositions with high thermal stability, but have issues with thermal stability under harsher environments, particularly with a significant decrease in tensile elongation at break after heating.

[0008] An object of the present invention is to solve the above-mentioned problems of the conventional art and to provide a thermoplastic resin composition, a fiber-reinforced resin substrate, and a molded article thereof, which have excellent thermal stability and mechanical properties. [Means for solving the problem]

[0009] The present invention was achieved as a result of studies aimed at solving the problems in the prior art described above, and has the following configuration. [1] A thermoplastic resin composition comprising (A) a thermoplastic resin having an electron-donating group and (B) a transition metal compound, the electron-donating group is at least one of an ether group, a sulfide group, a thiol group, an amino group, and an alkylamino group; The (B) transition metal compound includes (B1) a nickel compound and (B2) a copper compound, the (B2) copper compound having a complete decomposition temperature of 400°C or higher, and the (A) thermoplastic resin composition has a nickel content of 0.001 part by mass or more and 4 parts by mass or less and a copper content of 0.001 part by mass or more and 4 parts by mass or less, relative to 100 parts by mass of a thermoplastic resin having an electron-donating group. [2] (A) a thermoplastic resin having an electron-donating group, (B) a transition metal compound, and (C) an amine compound, the electron-donating group is at least one of an ether group, a sulfide group, a thiol group, an amino group, and an alkylamino group;and a melt viscosity retention rate after heating for 30 minutes at a temperature 70°C above the melting point of (A) thermoplastic resin having an electron-donating group of 90% or more and 7000% or less, wherein the thermoplastic resin having an electron-donating group (A) comprises (A1) polyarylene sulfide, and the (A1) polyarylene sulfide in the thermoplastic resin composition has a COOH group blocking rate represented by formula (I) of 30% or more, the (B) transition metal compound comprises (B1) a nickel compound or (B2) a copper compound, and the (B2) copper compound has a complete decomposition temperature of 400°C or more, and the (C) amine compound is a primary and / or secondary amine compound having a molecular weight of 5000 or less and a boiling point of 300°C or more, and the transition metal content is 0.001 part by mass or more and 8 parts by mass or less, and the (C) amine compound content is 0.01 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the (A1) polyarylene sulfide.

number

[0011] [4 ](D) fibrous filler is contained in an amount of 10 parts by mass or more and 400 parts by mass or less per 100 parts by mass of (A) thermoplastic resin having an electron donating group, 3 13. The thermoplastic resin composition according to any one of claims 1 to 12. [ 5 ] to a reinforcing fiber substrate in which a continuous (D) fibrous filler or a discontinuous (D) fibrous filler is dispersed, [1] to [ 3 13. A fiber-reinforced resin substrate impregnated with the thermoplastic resin composition according to any one of claims 1 to 12. [ 6 ][1]~[ 4

[0023] The thermoplastic resin composition according to any one of [ 5 ] A molded article obtained by molding the fiber-reinforced resin substrate described in the above. Effect of the Invention

[0012] According to the present invention, a thermoplastic resin composition having excellent thermal stability and mechanical properties can be obtained. [Brief description of the drawings]

[0013] [Figure 1] (B2-1) A diagram showing the results of thermogravimetric analysis of copper(II) chloride anhydride under specified conditions. [Diagram 2] (B'2-1) A diagram showing the results of thermogravimetric analysis of copper(II) nitrate trihydrate under specified conditions. [Diagram 3] FIG. 2 is a schematic diagram showing fiber-reinforced resin molded bodies welded together. [Figure 4] FIG. 2 is a schematic diagram of a molded article prepared for evaluating formability used in the examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail.

[0015] A first embodiment of the thermoplastic resin composition of the present invention is a thermoplastic resin composition comprising (A) a thermoplastic resin having an electron-donating group and (B) a transition metal compound, wherein the (B) transition metal compound comprises (B1) a nickel compound and (B2) a copper compound.

[0016] A second embodiment of the thermoplastic resin composition of the present invention comprises (A) a thermoplastic resin having an electron-donating group, (B) a transition metal compound, and (C) an amine compound, wherein (A) the thermoplastic resin having an electron-donating group comprises (A1) a polyarylene sulfide, (B) the transition metal compound comprises (B1) a nickel compound or (B2) a copper compound, and (B2) the copper compound has a complete decomposition temperature of 400°C or higher.

[0017] <(A) Thermoplastic resin having electron-donating group> The (A) thermoplastic resin having an electron-donating group included in the first embodiment of the thermoplastic resin composition of the present invention (hereinafter, may be simply referred to as "(A) thermoplastic resin") is not particularly limited as long as it is a thermoplastic resin having an electron-donating group described below.

[0018] The electron-donating group is a substituent that donates electrons to increase the electron density in the surroundings, and the electron-donating group in the present invention is limited to an electron-donating group having excellent coordination bond properties with (B1) a nickel compound and (B2) a copper compound having a complete decomposition temperature of 400° C. or higher. Specifically, the electron-donating group in the present invention is limited to an ether group, a sulfide group, a thiol group, an amino group, and an alkylamino group, and may contain two or more of these groups.

[0019] The thermoplastic resin having an electron-donating group (A) is not particularly limited as long as it is a thermoplastic resin having an ether group, a sulfide group, a thiol group, an amino group, or an alkylamino group. The thermoplastic resin having an electron-donating group (A) is, for example, polyamide, polyacetal, polyphenylene ether, polyaryl ether ketone, polyarylene sulfide, polyphenyl sulfone, polysulfone, polyamide imide, polyether sulfone, polyether imide, etc. Among these, polyamide, polyaryl ether ketone, polyarylene sulfide, polyphenyl sulfone, polysulfone, polyether sulfone, polyether imide are preferred from the viewpoint of exhibiting a particularly excellent thermal stabilization effect, and polyamide, polyaryl ether ketone, polyarylene sulfide are particularly preferred.

[0020] <(B1) Nickel compounds> The nickel compound contained in the first embodiment of the thermoplastic resin composition of the present invention is not particularly limited as long as it is a nickel compound. Nickel has a small ionic radius among transition metals and is characterized by being easily coordinated.

[0021] (B1) Nickel compounds include nickel carboxylates, halides, carbonates, hydroxides, oxides, sulfides, acetylacetone complexes, and alkoxides. Examples of carboxylic acids include formic acid, acetic acid, propionic acid, butyric acid, stearic acid, lactic acid, oleic acid, benzoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, and adipic acid. Examples of alkoxides include butoxide, propoxide, ethoxide, and methoxide. Among these, halides are preferred because they have high electron acceptability and are easily coordinated to the (A) thermoplastic resin. Examples of nickel halide salts include nickel chloride, nickel iodide, nickel bromide, and nickel fluoride. Among these, nickel chloride and nickel iodide are more preferred, and nickel iodide is even more preferred.

[0022] In the first embodiment of the thermoplastic resin composition of the present invention, the nickel content is 0.001 to 4 parts by mass relative to 100 parts by mass of the (A) thermoplastic resin. The nickel content is preferably 0.01 to 2 parts by mass, more preferably 0.1 to 1 part by mass. If the nickel content is less than 0.001 parts by mass, it is difficult to obtain an excellent heat stabilizing effect. If the nickel content is more than 4 parts by mass, the (B1) nickel compound is likely to aggregate, and it is not possible to obtain excellent heat stabilizing effects and mechanical properties.

[0023] The nickel content in the thermoplastic resin composition of the present invention is quantified by incinerating the thermoplastic resin composition, thermally decomposing the incinerated product with sulfuric acid or hydrofluoric acid, and then dissolving the incinerated product in dilute sulfuric acid or aqua regia to obtain a constant volume solution, which is then analyzed using an ICP mass spectrometer and an ICP atomic emission spectrometer.

[0024] The content of the thermoplastic resin (A) in the thermoplastic resin composition can be measured as follows: The thermoplastic resin composition is dissolved in a solvent that dissolves the thermoplastic resin (A), the insoluble matter is filtered, and the soluble matter is precipitated and recovered in a poor solvent. The content can be measured by qualitative and quantitative analysis such as high performance liquid chromatography using a solvent that dissolves the recovered matter. <(B2) Copper compounds having a complete decomposition temperature of 400°C or higher> The (B2) copper compound having a complete decomposition temperature of 400° C. or higher (hereinafter, may be simply referred to as “(B2) copper compound”) included in the first embodiment of the thermoplastic resin composition of the present invention is not particularly limited as long as it is a copper compound having a complete decomposition temperature of 400° C. or higher as described below. Copper has a small ionic radius among transition metals and is characterized by its ease of forming coordinate bonds.

[0025] Examples of the (B2) copper compound include metal salts such as copper carboxylates, halides, carbonates, hydroxides, oxides, sulfides, acetylacetone complexes, and alkoxides. Examples of the carboxylic acid include formic acid, acetic acid, propionic acid, butyric acid, stearic acid, lactic acid, oleic acid, benzoic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, and adipic acid. Examples of the alkoxide include butoxide, propoxide, ethoxide, and methoxide. Among these, in the first embodiment of the thermoplastic resin composition of the present invention, the (B2) copper compound is preferably a copper halide, since the complete decomposition temperature is likely to be 400° C. or higher. Examples of the copper halide salt include copper chloride, copper iodide, copper bromide, and copper fluoride. Among these, copper chloride and copper iodide are more preferable, and copper iodide is even more preferable.

[0026] (B2) The complete decomposition temperature of the copper compound is 400°C or higher. The complete decomposition temperature is the temperature at which the compound components other than copper in the copper compound are substantially almost completely decomposed or separated from the copper. This temperature can be measured by weighing a small amount of copper compound into a container and measuring the mass change while heating at a constant rate in an inert gas atmosphere using a thermogravimetric analyzer. The mass loss rate of the copper compound is measured while heating in a nitrogen atmosphere, and the complete decomposition temperature can be defined as the temperature at which the mass loss does not proceed any further. The temperature at which the mass loss does not proceed any further is the temperature at which the mass loss rate reaches 90% of the mass of the compound components other than copper in the copper compound, and is used to determine the complete decomposition temperature.

[0027] When the complete decomposition temperature of the (B2) copper compound is 400° C. or higher, even if the thermoplastic resin composition of the present invention is heated at a high temperature of less than 400° C., the ligands of the (B2) copper compound are not eliminated, and the copper is not reduced, so that the compound remains as a monovalent or divalent copper compound. This monovalent or divalent copper compound has electron-accepting properties and can accept and coordinate electrons from the electron-donating groups of the (A) thermoplastic resin.

[0028] On the other hand, when a thermoplastic resin composition contains a copper compound (B'2) having a similar copper content and a complete decomposition temperature of less than 400°C (hereinafter sometimes simply referred to as "copper compound (B'2)") instead of the copper compound (B2) having a copper content of 0.001 to 4 parts by mass per 100 parts by mass of the thermoplastic resin (A), depending on the temperature at which the thermoplastic resin composition is heated, the ligands of the copper compound (B'2) are eliminated and the copper is reduced to zero-valent copper. This zero-valent copper has electron donating properties, but since its coordination ability is not as high as that of nickel, it has poor coordination bonding properties with the thermoplastic resin.

[0029] In the first embodiment of the thermoplastic resin composition of the present invention, the copper content is 0.001 to 4 parts by mass relative to 100 parts by mass of the (A) thermoplastic resin. The copper content is preferably 0.01 to 2 parts by mass, more preferably 0.1 to 1 part by mass. If the copper content is less than 0.001 parts by mass, it is difficult to obtain an excellent heat stabilization effect. If the copper content is more than 4 parts by mass, the (B2) copper compound is likely to aggregate, and it is not possible to obtain excellent heat stabilization effect and mechanical properties.

[0030] In the first embodiment of the thermoplastic resin composition of the present invention, the total content of the thermoplastic resin (A), nickel, and copper is preferably 20% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 100% by mass or less.

[0031] The copper content in the thermoplastic resin composition of the present invention is quantified by incinerating the thermoplastic resin composition, thermally decomposing the incinerated product with sulfuric acid or hydrofluoric acid, and then dissolving the incinerated product in dilute sulfuric acid or aqua regia to obtain a constant volume solution, which is then analyzed using an ICP mass spectrometer and an ICP atomic emission spectrometer.

[0032] The reason why the first embodiment of the thermoplastic resin composition of the present invention exhibits excellent thermal stability and mechanical properties is not necessarily clear, but is speculated as follows. (A) Thermoplastic resin generates active peroxide radicals when heated at a temperature equal to or higher than the melting point in the presence of oxygen, and crosslinking or decomposition reactions proceed excessively starting from these peroxide radicals. As a result, the thermal stability and mechanical properties are also poor. It is speculated that by coordinating nickel and copper, which have high coordination bond ability, to the electron-donating group of the thermoplastic resin, the generation of peroxide radicals can be suppressed, and crosslinking or decomposition can be suppressed, that is, a thermoplastic resin composition having excellent thermal stability and mechanical properties can be obtained. It is also speculated that by coordinating nickel and copper to the electron-donating group of the (A) thermoplastic resin, molecular chains can be linked by coordination bonds, and a moderately crosslinked thermoplastic resin can be obtained, and mechanical properties can be further improved.

[0033] Although a thermal stabilization effect can be obtained when either the (B1) nickel compound or the (B2) copper compound is contained in the (A) thermoplastic resin, by containing the (B1) nickel compound and the (B2) copper compound in a specific ratio, a thermoplastic resin composition having significantly excellent thermal stability and mechanical properties can be obtained.

[0034] A second embodiment of the thermoplastic resin composition of the present invention comprises (A) a thermoplastic resin having an electron-donating group, (B) a transition metal compound, and (C) an amine compound, wherein (A) the thermoplastic resin having an electron-donating group comprises (A1) a polyarylene sulfide, (B) the transition metal compound comprises (B1) a nickel compound or (B2) a copper compound, and (B2) the copper compound has a complete decomposition temperature of 400°C or higher.

[0035] <(A1) Polyarylene sulfide> In the present invention, the polyarylene sulfide (A1) is a polymer containing preferably 90 mol % or more, more preferably 95 mol % or more, of the repeating unit represented by the general formula (II). If the repeating unit is less than 90 mol %, heat resistance is impaired, which is not preferable.

[0036] [ka]

[0037] Representative examples of (A1) polyarylene sulfide include polyarylene sulfide, polyarylene sulfide sulfone, polyarylene sulfide ketone, and random copolymers and block copolymers thereof. Two or more of these may be blended. Among these, polyphenylene sulfide containing 80 mol % or more of p-phenylene sulfide-derived units in all repeating units is more preferred, and polyphenylene sulfide containing 90 mol % or more is even more preferred.

[0038] The method for producing (A1) polyarylene sulfide is not particularly limited, and examples thereof include a method of reacting a dichloroaromatic compound with a sulfidizing agent in an organic polar solvent, a method of converting a cyclic polyarylene sulfide into a polyarylene sulfide by heating, and a method of melting and reacting a diiodo aromatic compound with sulfur element. The post-treatment of the polyarylene sulfide obtained by these methods is also not particularly limited, and may include a treatment of washing with a solvent to remove oligomer components, a treatment of reducing solvents and gas components by heating or devolatilization, a treatment of crosslinking under an oxygen atmosphere, and a treatment of melting the obtained polyarylene sulfide again to perform an additional reaction.

[0039] In the present invention, the (A1) polyarylene sulfide has a carboxyl group capable of reacting with the (C) amine compound described below.

[0040] <(B) Transition metal compound> The (B) transition metal compound included in the second embodiment of the thermoplastic resin composition of the present invention includes a (B1) nickel compound or a (B2) copper compound. In the second embodiment of the thermoplastic resin composition of the present invention, the (B) transition metal compound is alternatively selected from the (B1) nickel compound and the (B2) copper compound, and both are not used in combination.

[0041] In the second embodiment of the thermoplastic resin composition of the present invention, the transition metal content is 0.001 to 8 parts by mass relative to 100 parts by mass of (A1) polyarylene sulfide. The transition metal content is preferably 0.001 to 4 parts by mass, more preferably 0.006 to 1 part by mass. When the transition metal content is less than 0.001 parts by mass relative to 100 parts by mass of (A1) polyarylene sulfide, it is difficult to obtain an excellent thermal stabilization effect. In addition, when the transition metal content is more than 8 parts by mass, aggregation of the transition metal is likely to occur, and excellent thermal stabilization effect and mechanical properties cannot be obtained. Here, the transition metal content in the thermoplastic resin composition corresponds to the transition metal ion content in (B) transition metal compound, and is measured by ICP mass spectrometry or ICP atomic emission spectrometry as follows.

[0042] The content of the transition metal in the thermoplastic resin composition of the present invention is quantified by incinerating the thermoplastic resin composition, thermally decomposing the incinerated product with sulfuric acid or hydrofluoric acid, and then dissolving the incinerated product in dilute sulfuric acid or aqua regia to obtain a constant volume solution, which is then analyzed using an ICP mass spectrometer and an ICP atomic emission spectrometer.

[0043] <(B1) Nickel compounds> The (B1) nickel compound contained in the second embodiment of the thermoplastic resin composition of the present invention refers to the same as the (B1) nickel compound contained in the first embodiment. The (B1) nickel compound decomposes completely at a temperature equal to or higher than the melting point of the (A1) polyarylene sulfide. The decomposition temperature is preferably 350°C or higher. When the temperature is 350°C or higher, even if the thermoplastic resin composition is heated at a high temperature lower than 350°C, the ligands of the (B1) nickel compound are not eliminated, and the nickel is not reduced, so that the compound remains as a monovalent to trivalent nickel compound. The monovalent to trivalent nickel compound has high electron accepting property and is likely to accept and coordinate electrons from the electron donating group at the end of the (A1) polyarylene sulfide.

[0044] <(B2) Copper compound> The copper compound (B2) contained in the thermoplastic resin composition of the second embodiment of the present invention is the same as the copper compound (B2) used in the first embodiment.

[0045] <(C) Amine Compound> The amine compound contained in the second embodiment of the thermoplastic resin composition of the present invention is not particularly limited as long as it reacts with the carboxyl group of the polyarylene sulfide (A1), but it is preferably a primary and / or secondary amine compound having a molecular weight of 5000 or less and a boiling point of 200° C. or more. The boiling point is more preferably 300° C. or more. In the present invention, the boiling point refers to the boiling point at 1 atmospheric pressure.

[0046] When the molecular weight is 5000 or less, the reactivity with the carboxyl group of the (A1) polyarylene sulfide is improved, and when the boiling point is 200°C or more, preferably 300°C or more, volatilization can be suppressed at the processing temperature of the (A1) polyarylene sulfide, and excellent thermal stability and mechanical properties can be obtained. In addition, primary and / or secondary amines are preferable because they have reactivity with the carboxyl group of the (A1) polyarylene sulfide. Note that the primary and / or secondary amine compound refers to an amine compound having a primary amino group and / or a secondary amino group in one amine compound. Specific examples include o-phenylenediamine (boiling point 252°C / primary amine), p-phenylenediamine (boiling point 267°C / primary amine), 1,5-diaminonaphthalene (boiling point 210°C / primary amine), and more preferably carbazole (boiling point 354°C / secondary amine), 4,4-diphenylcarbazole (boiling point 575°C / secondary amine), and phenothiazine (boiling point 379°C / secondary amine).

[0047] In the second embodiment of the thermoplastic resin composition of the present invention, the content of the amine compound (C) is 0.01 parts by mass or more and 5 parts by mass or less relative to 100 parts by mass of the polyarylene sulfide (A1). The content of the amine compound (C) is preferably 0.5 parts by mass or more and 3 parts by mass or less. When the content of the amine compound (C) is less than 0.01 parts by mass relative to 100 parts by mass of the polyarylene sulfide (A1), it is difficult to obtain an excellent thermal stabilization effect. In addition, when the content of the amine compound (C) is more than 5 parts by mass, it is an excessive amount relative to the polyarylene sulfide (A1), and a large amount of unreacted amine is present, which may lead to a decrease in thermal stability.

[0048] In the second embodiment of the thermoplastic resin composition of the present invention, the total content of the (A1) polyarylene sulfide, the transition metal, and the (C) amine compound is preferably 20% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 100% by mass or less.

[0049] The content of the amine compound (C) in the thermoplastic resin composition of the present invention is measured as follows. The thermoplastic resin composition is dissolved in a solvent in which the polyarylene sulfide (A1) and the amine compound (C) are soluble, such as chloronaphthalene, and the insoluble matter is filtered off, and the soluble matter is precipitated and recovered in a poor solvent. The recovered polyarylene sulfide (A1) and the amine compound (C) that has reacted with the polyarylene sulfide (A1) are measured by quantitative and qualitative analysis such as FT-IR, and the unreacted amine compound (C) dissolved in the poor solvent is measured by quantitative and qualitative analysis such as high performance liquid chromatography.

[0050] The reason why the thermoplastic resin composition according to the second embodiment of the present invention exhibits excellent thermal stability and mechanical properties is not necessarily clear, but is presumed to be as follows.

[0051] When polyarylene sulfide (A1) is heated in the presence of oxygen at a temperature equal to or higher than the melting point, the carboxyl group undergoes cyclization and generates active peroxide radicals, which then initiate excessive crosslinking or decomposition reactions. This results in poor thermal stability and poor mechanical properties. It is speculated that by reacting polyarylene sulfide (A1) with an amine compound (C) to modify the carboxyl group, and further by coordinating a transition metal compound (B) with high coordination bond ability to the electron-donating group of polyarylene sulfide (A1), it is possible to suppress the generation of peroxide radicals and suppress crosslinking or decomposition, i.e., obtain a thermoplastic resin composition with excellent thermal stability and mechanical properties.

[0052] In addition, the (B) transition metal compound also acts as a catalyst to promote the amidation reaction between the carboxyl groups of the (A1) polyarylene sulfide and the (C) amine compound, and it is therefore assumed that by increasing the reaction rate, the thermal stability and mechanical properties can be further improved.

[0053] In the second embodiment of the thermoplastic resin composition of the present invention, the melt viscosity retention rate after heating for 30 minutes at the melting point of (A) the thermoplastic resin having an electron donating group + 70°C is 90% or more and 7000% or less. If the melt viscosity retention rate is less than 90%, the main chain of (A1) polyarylene sulfide is decomposed, and the mechanical properties are reduced. If the melt viscosity retention rate is more than 7000%, crosslinking due to thermal degradation progresses excessively, and the mechanical properties are reduced. As a means for making the melt viscosity retention rate 90% or more and 7000% or less, a method of adding (B) a transition metal compound and (C) a primary and / or secondary amine compound having a boiling point of 200°C or more to (A) the thermoplastic resin having an electron donating group can be preferably used.

[0054] In the second embodiment of the thermoplastic resin composition of the present invention, the blocking rate of COOH groups represented by formula (I) of polyarylene sulfide (A1) in the thermoplastic resin composition is preferably 30% or more. When it is 30% or more, the generation of peroxide radicals can be suppressed and an excellent thermal stabilization effect can be obtained. Here, X represents the amount of carboxyl groups in polyarylene sulfide (A1), and Y represents the amount of carboxyl groups in polyarylene sulfide (A1) in the thermoplastic resin composition.

[0055]

number

[0056] The amount of carboxyl groups in the polyarylene sulfide (A1) or the polyarylene sulfide (A1) in the thermoplastic resin composition is calculated from the absorption peak derived from the carboxyl groups by subjecting an amorphous film obtained by melt pressing to FT-IR measurement.

[0057] <(D) Fibrous filler> The thermoplastic resin composition of the present invention preferably contains (D) fibrous filler in an amount of 10 parts by mass to 400 parts by mass based on 100 parts by mass of (A) thermoplastic resin having an electron-donating group. By containing (D) fibrous filler, mechanical properties can be further improved.

[0058] (D) Examples of the fibrous filler include glass fiber, carbon fiber, aramid fiber, polyamide fiber, polyester fiber, vinylon fiber, cotton, hemp fiber, kenaf fiber, bamboo fiber, rayon, steel fiber, aluminum fiber, etc. Among these, glass fiber and carbon fiber are preferred, and carbon fiber is more preferred, because they have high affinity with thermoplastic resins and can further improve mechanical properties.

[0059] (D) The shape of the fibrous filler can be, for example, continuous fiber, short fiber such as chopped strand, or whisker.

[0060] As described above, the content of the (D) fibrous filler in the thermoplastic resin composition is preferably 10 parts by mass or more and 400 parts by mass or less per 100 parts by mass of the (A) thermoplastic resin. If the content is 10 parts by mass or more, the mechanical properties of the thermoplastic resin composition can be improved. Also, if the content is 400 parts by mass or less, the moldability is less likely to decrease.

[0061] The method for measuring the content of the (D) fibrous filler can be as follows: The thermoplastic resin composition is filtered using a solvent that dissolves the (A) thermoplastic resin, and the insoluble matter is removed, and the (D) fibrous filler and (B) transition metal compound are recovered as the filtrate. The (B) transition metal compound is further removed using a solvent that dissolves the compound, and the fibrous filler is recovered and washed, after which the mass is measured.

[0062] <Fiber-reinforced resin substrate> The fiber-reinforced resin substrate of the present invention is prepared by impregnating a continuous (D) fibrous filler or a reinforcing fiber substrate in which discontinuous (D) fibrous filler is dispersed with the thermoplastic resin composition of the present invention.

[0063] That is, the fiber reinforced resin substrate of the present invention can be exemplified by the following two embodiments. The first embodiment of the fiber reinforced resin substrate of the present invention is obtained by impregnating a continuous fibrous filler (D) with the thermoplastic resin composition of the present invention. The second embodiment of the fiber reinforced resin substrate of the present invention is obtained by impregnating a reinforcing fiber substrate having a discontinuous fibrous filler (D) dispersed therein with the thermoplastic resin composition of the present invention.

[0064] The continuous (D) fibrous filler in the first embodiment refers to a fiber-reinforced resin substrate in which the reinforcing fibers are uninterrupted. Examples of the form and arrangement of the continuous (D) fibrous filler include those aligned in one direction, woven fabric (cloth), knitted fabric, braided cord, tow, etc. Among them, it is preferable that the continuous (D) fibrous filler is aligned in one direction, since this can efficiently improve the mechanical properties in a specific direction.

[0065] The reinforcing fiber substrate in which the discontinuous (D) fibrous filler is dispersed in the second embodiment refers to a mat-like fiber reinforced resin substrate in which the fibrous filler is cut and dispersed. The reinforcing fiber substrate can be obtained by any method, such as a wet method in which fibers are dispersed in a solution and then produced in a sheet form, or a dry method using a carding device or an airlaid device. From the viewpoint of productivity, a dry method using a carding device or an airlaid device is preferred. The number average fiber length of the discontinuous (D) fibrous filler in the reinforcing fiber substrate is preferably 3 to 100 mm. If the number average fiber length of the discontinuous fibers is 3 mm or more, the reinforcing effect of the discontinuous fibers is sufficiently exhibited, and the mechanical strength of the obtained fiber reinforced resin substrate can be further improved. The number average fiber length of the discontinuous fibers is more preferably 5 mm or more. On the other hand, if the number average fiber length of the discontinuous fibers is 100 mm or less, the flowability during molding can be further improved. The number average fiber length of the discontinuous fibers is more preferably 50 mm or less, and even more preferably 30 mm or less.

[0066] The number average fiber length of the discontinuous fibers can be determined by the following method. First, a sample of 100 mm x 100 mm is cut out from the fiber-reinforced resin substrate, and the cut sample is heated in an electric furnace at 600°C for 1.5 hours to burn off the matrix resin. 400 discontinuous reinforcing fiber bundles are randomly sampled from the fiber-reinforced resin substrate thus obtained. The fiber length of the discontinuous reinforcing fiber bundles thus sampled is measured in 1 mm increments using a vernier caliper, and the number average fiber length (Ln) can be calculated by the following formula.

[0067] Ln=ΣLi / 400 (Li: measured fiber length (i = 1, 2, 3, 400) (unit: mm)).

[0068] The number average fiber length of the discontinuous fibers can be adjusted to the above range by cutting the fibers to a desired length during the production of the reinforcing fiber substrate. There is no particular restriction on the orientation of the discontinuous fiber mat, but from the viewpoint of moldability, it is preferable that the fibers are isotropically dispersed.

[0069] In the first embodiment, the method of impregnating the continuous (D) fibrous filler with the thermoplastic resin composition includes, for example, a film method in which a film-like thermoplastic resin composition is melted and pressurized to impregnate a reinforcing fiber bundle with the thermoplastic resin composition, a comingle method in which a fibrous thermoplastic resin composition is mixed with a reinforcing fiber bundle, and then the fibrous thermoplastic resin composition is melted and pressurized to impregnate the reinforcing fiber bundle with the thermoplastic resin composition, a powder method in which a powdered thermoplastic resin composition is dispersed in the gaps between the fibers in the reinforcing fiber bundle, and then the powdered thermoplastic resin composition is melted and pressurized to impregnate the reinforcing fiber bundle, and a pultrusion method in which the reinforcing fiber bundle is immersed in the molten thermoplastic resin composition and pressurized to impregnate the reinforcing fiber bundle with the thermoplastic resin composition. The pultrusion method is preferred because it can produce a wide variety of fiber-reinforced resin substrates with various thicknesses and fiber volume contents.

[0070] In the second embodiment, examples of the method for impregnating the reinforcing fiber substrate having the discontinuous (D) fibrous filler dispersed therein with the thermoplastic resin composition include a method of supplying the thermoplastic resin composition by an extruder to impregnate the reinforcing fiber substrate, a method of dispersing a powdered thermoplastic resin composition in a fiber layer of the reinforcing fiber substrate and melting it, a method of forming the thermoplastic resin composition into a film and laminating it with the reinforcing fiber substrate, a method of dissolving the thermoplastic resin composition in a solvent and impregnating the reinforcing fiber substrate in the form of a solution and then volatilizing the solvent, a method of fiberizing the thermoplastic resin composition to form a mixed yarn with discontinuous fibers, and a method of laminating using a melt-blown nonwoven fabric.

[0071] In addition, the fiber reinforced resin substrate of the present invention can be selected according to the desired impregnation property depending on the usage and purpose. For example, prepreg with higher impregnation property, semi-preg with half impregnation, fabric with low impregnation property, etc. are included. In general, the more impregnated the molding material, the more preferable it is because a molded product with excellent mechanical properties can be obtained by molding for a short time.

[0072] The fiber-reinforced resin substrate impregnated with the thermoplastic resin composition of the present invention has excellent thermal stability, and therefore has excellent bonding strength when the fiber-reinforced resin substrates are bonded together. This is thought to be because the fiber-reinforced resin substrates are heated in an oxygen atmosphere when bonded together, and oxidation deterioration on the substrate surface can be suppressed, resulting in excellent bonding strength.

[0073] <Molded products> The molded article of the present invention is obtained by molding the thermoplastic resin composition of the present invention or the fiber-reinforced resin substrate of the present invention.

[0074] <Method of producing thermoplastic resin composition> The method for producing the thermoplastic resin composition of the present invention is not particularly limited, but for example, in the first embodiment, (A) thermoplastic resin, (B1) nickel compound, and (B2) copper compound are dry blended and fed from the main feeder of an extruder. In the second embodiment, (A1) polyarylene sulfide, (B1) nickel compound or (B2) copper compound, and (C) amine compound are dry blended and fed from the main feeder of an extruder. Furthermore, a preferred method is to feed (D) fibrous filler from a side feeder of an extruder as necessary, and melt knead at a temperature equal to or higher than the melting point of (A) thermoplastic resin.

[0075] <Method of molding thermoplastic resin composition> The method for molding the thermoplastic resin composition of the present invention is not particularly limited, but examples thereof include injection molding, extrusion molding, compression molding, etc. Molded articles such as molded products, sheets, and films can be obtained by these molding methods.

[0076] Other molding methods include a press molding method in which a material obtained by laminating fiber-reinforced resin substrates impregnated with a thermoplastic resin composition in an arbitrary configuration is heated and pressurized; an autoclave molding method in which the material is placed in an autoclave and heated and pressurized; a bagging molding method in which the material is wrapped in a film or the like, the inside is reduced pressure, and the material is heated in an oven while being pressurized at atmospheric pressure; and a wrapping tape method in which tape is wrapped around the material under tension and the material is heated in an oven.

[0077] As the press molding method, a hot press method in which a fiber-reinforced resin substrate is placed in a mold in advance, pressurized and heated while the mold is closed, and then the mold is cooled to cool the fiber-reinforced resin substrate while the mold is still closed, to obtain a molded product, or stamping molding, a method in which a fiber-reinforced resin substrate is heated in advance to a temperature equal to or higher than the melting temperature of the thermoplastic resin by a heating device such as a far-infrared heater, a heating plate, a high-temperature oven, or a dielectric heater, and the thermoplastic resin is placed in a melted and softened state on a mold that will become the lower surface of the molding die, then the mold is closed to close the mold, and thereafter the mold is pressurized and cooled, can be used. There are no particular limitations on the press molding method, but stamping molding is preferable from the viewpoint of accelerating the molding cycle and increasing productivity.

[0078] <Other ingredients> If desired, the thermoplastic resin composition of the present invention may contain inorganic fillers other than fibrous fillers such as titanium oxide and calcium carbonate, antioxidants, heat stabilizers, ultraviolet absorbers, colorants, and the like.

[0079] <Application examples of molded products> Molded articles obtained from the thermoplastic resin composition of the present invention are useful in a wide range of applications, including electronic component applications such as connectors, coils, sensors, LED lamps, sockets, resistors, relay cases, small switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, semiconductors, liquid crystal, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, and computer-related parts; electrical equipment component applications such as generators, electric motors, transformers, current transformers, voltage regulators, rectifiers, inverters, relays, power contacts, switches, circuit breakers, knife switches, other-pole rods, and electrical component cabinets; VTR parts, television parts, irons, hair dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as audio / laser discs (registered trademark), compact discs, and DVDs; lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and the like; and home and office electrical appliance parts applications such as office computers. parts for motors, telephones, facsimile machines, copiers, cleaning tools, motor parts, lighters, typewriters, and other machine-related parts, microscopes, binoculars, cameras, watches, and other optical equipment, precision machinery parts, alternator terminals, alternator connectors, IC regulators, light dimmer potentiometer bases, exhaust gas valves and other valves, fuel-related, exhaust and intake pipes, air intake nozzle snorkels, intake manifolds, fuel pumps, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, air flow meters, brake pad wear sensors, air conditioner thermostat bases, heating hot air flow control valves, radiator motor brush holders, water pump impellers, turbine vanes, wiper motor parts, distributors, starter switches, starter relays,They can be used in a wide range of applications, including transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, fuel-related electromagnetic valve coils, fuse connectors, horn terminals, electrical component insulation plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other automotive and vehicle-related parts, as well as various aerospace applications. EXAMPLES

[0080] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. In addition, Examples 23 and 25 should be read as Reference Examples 23 and 25. The resins and additives used in the examples and comparative examples are shown below.

[0081] <(A) Thermoplastic resin having electron-donating group> (A-1) Polyphenylene sulfide (Reference Example 1, melting point 280°C) (A-2) Polyether ether ketone (Victrex (registered trademark) 90G, melting point: 343°C) (A-3) Polyamide 66 (Toray "Amilan (registered trademark)" CM3001, melting point 260°C) (Reference example 1) In a 70-liter autoclave equipped with a stirrer and a bottom plug valve, 8.27 kg (70.00 mol) of 47.5% sodium hydrosulfide, 2.94 kg (70.63 mol) of 96% sodium hydroxide, 11.45 kg (115.50 mol) of N-methyl-2-pyrrolidone (NMP), 1.89 kg (23.1 mol) of sodium acetate, and 5.50 kg of ion-exchanged water were charged, and the mixture was gradually heated to 245°C over about 3 hours while passing nitrogen through it at normal pressure. After distilling out 9.77 kg of water and 0.28 kg of NMP, the reaction vessel was cooled to 200°C. The amount of water remaining in the system per mole of the charged amount of alkali metal sulfide was 1.06 mol, including the water consumed in the hydrolysis of NMP. The amount of hydrogen sulfide scattered was 0.02 mol per mole of the charged amount of alkali metal sulfide.

[0082] After cooling the reaction vessel to 200°C, 10.42 kg (70.86 mol) of p-dichlorobenzene and 9.37 kg (94.50 mol) of NMP were added, the reaction vessel was sealed under nitrogen gas, and the temperature was raised from 200°C to 270°C at a rate of 0.6°C / min while stirring at 240 rpm, and the reaction was carried out at 270°C for 140 minutes. Then, 2.40 kg (133 mol) of water was injected while cooling from 270°C to 250°C over 15 minutes. Then, the mixture was gradually cooled from 250°C to 220°C over 75 minutes, and then quenched to near room temperature, and the contents were removed.

[0083] The contents were diluted with about 35 liters of NMP, stirred at 85°C for 30 minutes as a slurry, and filtered through an 80 mesh wire mesh (opening 0.175 mm) to obtain a solid. The obtained solid was washed and filtered with about 35 liters of NMP in the same manner. The obtained solid was added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh to recover the solid. This operation was repeated three times in total. The obtained solid and 32 g of acetic acid were added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh. The obtained solid was further added to 70 liters of ion-exchanged water, stirred at 70°C for 30 minutes, and then filtered through an 80 mesh wire mesh to recover the solid. The solid thus obtained was dried at 120°C under a nitrogen stream to obtain a dried polyphenylene sulfide resin. The mass average molecular weight was 48,600.

[0084] <Thermoplastic resin having no electron-donating group> Polyethylene terephthalate (PET): Toray F20-S, melting point 255℃.

[0085] <(B1) Nickel compounds> (B1-1) Nickel(II) iodide hexahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B1-2) Nickel(II) formate dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B1-3) A 3 mass% aqueous solution of nickel (II) iodide hexahydrate.

[0086] <(B2) Copper compounds with a complete decomposition temperature of 400°C or higher> (B2-1) Copper(II) chloride anhydrous (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B2-2) Copper(I) iodide anhydrous (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (B2-3) A 3% by mass aqueous solution of copper(II) chloride dihydrate.

[0087] <(B'2) Copper compounds having a complete decomposition temperature of less than 400°C> (B'2-1) Copper(II) nitrate trihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) <(C) Amine Compound> (C-1) Phenothiazine (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (Molecular weight 199, boiling point 371℃) (C-2) p-Phenylenediamine (Fujifilm Wako Pure Chemical Industries, Ltd.) (Molecular weight 108, boiling point 267℃) (C-3) Octylamine (Fujifilm Wako Pure Chemical Industries, Ltd.) (Molecular weight 129, boiling point 176℃) (C-4) Amine-modified elastomer Tuftec MP10 (manufactured by Asahi Kasei Corporation) (Molecular weight>5000, boiling point>300℃) <(D) Fibrous filler> (D-1) Carbon fiber "TORAYCA (registered trademark)" cut fiber TV14-006 (manufactured by Toray Industries, Inc.) (D-2) Discontinuous carbon fiber mat Toray Industries, Inc.'s "TORAYCA (registered trademark)" T700S-12k carbon fiber chopped yarn cut to a length of 20 mm was introduced into a carding device, and the resulting web was cross-lapped to a weight of 100 g / m 2 The carbon fiber sheet thus obtained was placed in a press and pressed at a pressure of 20 MPa for 5 seconds to obtain a discontinuous carbon fiber mat.

[0088] (D-3) Carbon fiber bundle (Toray Industries, Inc. "TORAYCA (registered trademark)" T700S-12k) <Method of producing thermoplastic resin composition> Among the raw materials shown in each of the examples and comparative examples in Tables 1, 2, 4, and 5, the raw materials except for (D-1) carbon fiber were dry-blended in the compositions shown in Tables 1, 2, 4, and 5, and fed from the main feeder of a twin-screw extruder (TEX30α manufactured by Japan Steel Works, Ltd.), and (D-1) carbon fiber was fed from a side feeder (installed at a position 0.35 from the upstream side when the total length of the screw is 1.0), and melt-kneaded at a cylinder temperature of 320 ° C (380 ° C for Example 11 and Comparative Example 9, 300 ° C for Example 12 and Comparative Examples 10 to 12) and a screw rotation speed of 200 rpm. The gut discharged from the die was immediately cooled in a water bath, pelletized by a strand cutter, and vacuum dried at 120 ° C (170 ° C for Example 11 and Comparative Example 9, 80 ° C for Example 12 and Comparative Examples 10 to 12) for 12 hours.

[0089] <Method for producing discontinuous fiber reinforced resin substrate impregnated with thermoplastic resin composition> Of the raw materials shown in each of the Examples and Comparative Examples in Tables 3 and 6, the raw materials except for (D-2) discontinuous carbon fiber mat were dry blended in the composition shown in the table, charged into the hopper of a single-screw extruder heated to 320°C, melt-kneaded, and then extruded from a film die into a film having a thickness of 100 μm.

[0090] (D-2) The winding direction of the discontinuous carbon fiber mat was set to 0 °, and 12 discontinuous fiber mats were laminated so as to be (0 ° / 90 ° / 0 ° / 90 ° / 0 ° / 90 °) s, and the thermoplastic resin composition film was laminated in the laminated discontinuous carbon fiber mat so that the mass ratio of the carbon fiber and the thermoplastic resin composition film was 50:50, and then the whole was sandwiched between stainless steel plates, preheated at 350 ° C. for 90 seconds, and hot pressed at 350 ° C. for 180 seconds while applying a pressure of 2.0 MPa. Then, it was cooled to 50 ° C. under pressure to obtain a fiber reinforced resin substrate having a thickness of 2 mm.

[0091] <Method for producing continuous fiber reinforced resin substrate impregnated with thermoplastic resin composition> Among the raw materials shown in each of the examples and comparative examples in Tables 3 and 6, the raw materials except for the carbon fiber bundle (D-3) were dry-blended in the composition shown in the table, and fed into the hopper of a single-screw extruder heated to 320°C. The gut discharged from the die after melt-kneading was immediately cooled in a water bath, pelletized by a strand cutter, and vacuum-dried at 120°C for 12 hours. 16 bobbins wound with the carbon fiber bundle (D-3) were prepared, and the carbon fiber bundle was continuously fed from each bobbin through a yarn guide. The continuously fed carbon fiber bundle was impregnated with the resin composition pellets obtained by the above-mentioned method, which were supplied in a fixed amount from a filled feeder, in an impregnation die heated to 320°C. The carbon fiber impregnated with the resin composition in the impregnation die was continuously pulled out from the nozzle of the impregnation die using a take-up roll at a pull-out speed of 1 m / min. The pulled carbon fiber bundle passed through a cooling roll to cool and solidify the resin composition, and was wound up on a winder as a continuous fiber-reinforced resin substrate. The resulting fiber-reinforced resin substrate had a thickness of 0.08 mm, a width of 50 mm, and the reinforcing fibers were aligned in one direction, resulting in a continuous fiber-reinforced resin substrate with a volume content of 60%. Six 0.08 mm thick continuous fiber-reinforced resin substrates were then stacked in the same direction and pressed at 15 bar for 20 minutes in a press machine heated to 320°C to obtain a laminate of continuous fiber-reinforced resin substrates with a thickness of 0.45 mm.

[0092] <Method of evaluating thermoplastic resin composition> The evaluation methods used in each of the examples and comparative examples will be described below.

[0093] (1) Transition metal content in thermoplastic resin composition The thermoplastic resin composition pellets were incinerated, and the incinerated product was decomposed by heating with sulfuric acid and hydrofluoric acid in a sealed container. The solution obtained by dissolving the incinerated product in aqua regia was measured by an ICP-MS (inductively coupled plasma mass spectrometer: ELEMENT manufactured by Thermoquest).

[0094] (2) Complete decomposition temperature of copper compounds Approximately 10 mg of the copper compound alone was weighed out, and after being held at 50°C for 1 minute under a nitrogen stream, the temperature was increased from 50°C to 500°C at a rate of 10°C / min using a thermogravimetric analyzer (TGA7 manufactured by PerkinElmer), and the mass loss was measured when the mass at 50°C was taken as 100%.

[0095] As an example, the results of thermogravimetric analysis of (B2-1) copper (II) chloride anhydride under the above conditions are shown in Figure 1. Similarly, the results of thermogravimetric analysis of (B'2-1) copper (II) nitrate trihydrate under the above conditions are shown in Figure 2. The horizontal axis represents temperature T (℃), and the vertical axis represents mass fraction W (%). In copper (II) chloride anhydride, chlorine equivalent to 52.7 mass% of the total mass calculated from the molecular weight is volatilized. The complete decomposition temperature is defined as the temperature at which the mass reduction rate reaches 90% of the mass of the compound components excluding copper in the copper compound. Therefore, the temperature at which a mass reduction of 47 mass%, which is 90% of 52.7 mass%, is observed is the complete decomposition temperature of copper (II) chloride anhydride. In copper (II) chloride anhydride, a mass reduction of 47 mass% was not observed at measurement temperatures up to 500 °C. Therefore, the complete decomposition temperature of copper (II) chloride anhydride is 500 °C or higher. On the other hand, in the case of copper (II) nitrate trihydrate, 22.3% by mass of the trihydrate calculated from the molecular weight is first evaporated (reference number 1 in Figure 2), and then 51.3% by mass of nitric acid is evaporated (reference number 2 in Figure 2). The complete decomposition temperature is defined as the temperature at which the mass reduction rate reaches 90% of the mass of the compound components excluding copper in the copper compound. The portion excluding copper in copper (II) nitrate trihydrate is 73.6% by mass, so 90% of that is 66% by mass. Therefore, the temperature at which a mass reduction of 66% by mass is observed is the complete decomposition temperature of copper (II) nitrate trihydrate. From Figure 2, the complete decomposition temperature of copper (II) nitrate trihydrate is 282°C.

[0096] (3) Melt viscosity measurement before and after heating The above thermoplastic resin composition pellets were freeze-pulverized / vacuum-dried and used as a sample for measuring melt viscosity before heating. The vacuum drying conditions were 120°C (170°C for Example 11 and Comparative Example 9, and 80°C for Example 12 and Comparative Examples 10 to 12) for 12 hours. In addition, about 50 mg of the freeze-pulverized / vacuum-dried sample was piled flatly on a 25mm x 7mm x 7mm micro aluminum dish (manufactured by Alpha Purchase) to a depth of about 300μm, and heated in an electric furnace under air at the melting point of (A) thermoplastic resin + 70°C for 30 minutes, and the sample after heating was freeze-pulverized / vacuum-dried and used as a sample for measuring melt viscosity after heating. The closer the melt viscosity retention rate before and after heating is to 100%, the more excellent the thermal stability is. The melt viscosity measurement conditions are as follows.

[0097] Apparatus: Rheometer (Anton Paar Physica MCR501) Atmosphere: Nitrogen flow Measurement temperature: (A) Melting point of thermoplastic resin + 70℃ Angular frequency: 6.28rad / sec Sample size: 0.7g Melt viscosity: Complex viscosity after 5 minutes residence under the above conditions.

[0098] (4) Tensile properties before and after heating The above thermoplastic resin composition pellets were freeze-pulverized / vacuum-dried using a small injection molding machine (HaakeMiniJetPro manufactured by Thermo Fisher Scientific) under the conditions of a cylinder temperature of 350 ° C. (380 ° C. for Example 11 and Comparative Example 9, 300 ° C. for Example 12 and Comparative Examples 10 to 12) and a mold temperature of 120 ° C. (170 ° C. for Example 11 and Comparative Example 9, 80 ° C. for Example 12 and Comparative Examples 10 to 12), and were injection-molded into dumbbells conforming to the ISO527-2-5A standard to obtain molded articles for tensile tests before heating. In addition, about 50 mg of the freeze-pulverized / vacuum-dried sample was piled flatly on a 25 mm × 7 mm × 7 mm micro aluminum dish (manufactured by Alpha Purchase) to a depth of about 300 μm, and heated in an electric furnace under air at the melting point of the thermoplastic resin (A) + 70 ° C. for 30 minutes, and the sample after heating was freeze-pulverized / vacuum-dried and molded under the above molding conditions to obtain molded articles for tensile tests after heating. The closer to 100% the tensile strength retention rate and tensile breaking elongation retention rate before and after heating are, the more excellent the thermal stability is. The tensile test conditions are as follows.

[0099] Equipment: Universal mechanical testing machine (Shimadzu Autograph AG-20kNX) Atmosphere: 23℃×50%RH Chuck distance: 50mm Distance between gauge lines: 20mm Pulling speed: 5mm / min.

[0100] (5) Carboxyl group measurement The amount of carboxyl groups in the polyarylene sulfide (A1) and the polyarylene sulfide (A1) in the thermoplastic resin composition was calculated using a Fourier transform infrared spectrometer (hereinafter abbreviated as FT-IR). First, benzoic acid was measured as a standard substance by FT-IR, and the absorption at 3066 cm, which is the absorption of the C-H bond of the benzene ring, was obtained. -1 The absorption intensity of the peak (b1) and the absorption of the carboxyl group at 1704 cm -1The absorption intensity (c1) of the peak was read, and the amount of carboxyl groups (U1) per benzene ring unit, (U1) = (c1) / [(b1) / 5], was calculated. Next, the (A1) polyarylene sulfide and thermoplastic resin composition were melt-pressed at 320°C for 1 minute, and then quenched to obtain an amorphous film, which was then subjected to FT-IR measurement. -1 Absorption intensity (b2) and 1704cm -1 The absorption intensity (c2) of was read, and the amount of carboxyl groups per benzene ring unit (U2), (U2) = (c2) / [(b2) / 4], was calculated. (A1) The carboxyl group content per 1 g of polyarylene sulfide and thermoplastic resin composition was calculated from the following formula. (A1) Carboxyl Group Amount (μmol / g) of Polyarylene Sulfide and Thermoplastic Resin Composition =(U2) / (U1) / 108.161×1000000.

[0101] (6) Welding test The discontinuous fiber reinforced resin substrate obtained by the above manufacturing method was cut to dimensions of 300 mm x 400 mm x 2 mm, preheated until the temperature at the center of the substrate reached 350°C, and then placed on a press platen heated to 190°C. Pressurized at 10 MPa for 30 seconds, the substrate was stamped to obtain a discontinuous fiber reinforced resin molded body, which was then used for welding.

[0102] The same type of discontinuous fiber-reinforced resin molded body (length 100 mm, width 25 mm, thickness 2 mm) was stacked as shown in Figure 3 and welded by vibration welding by applying a surface pressure of 1.6 MPa to an area with a width of 25 mm and a welding allowance of 12.5 mm.

[0103] (7) Tensile test of welded body It was measured by a lap shear test (shear test) according to JIS K6851. The specimens were pulled in opposite directions to apply a shear load, and the tensile strength was measured when the joint broke or deformed by a certain amount (e.g., interfacial fracture) to quantitatively evaluate the joint strength.

[0104] (8) Formability The laminate of the continuous fiber reinforced resin substrate obtained by the above manufacturing method was cut to a thickness of 0.45 mm, a width of 13 mm, and a length of 125 mm. Using a press machine (SA303 manufactured by Tester Sangyo) adjusted to 240 ° C, a laminate (6 shown in FIG. 4) preheated until the substrate center temperature reached 340 ° C was placed between a mold consisting of an upper mold (reference number 4 in FIG. 4) and a lower mold (reference number 5 in FIG. 4) with an uneven shape as shown in FIG. 4, and maintained at a pressure of 1.5 MPa for 10 minutes. The mold was transferred to a press machine (SA303 manufactured by Tester Sangyo) adjusted to 30 ° C and cooled, and a molded product deformed along the shape of the mold was obtained. The depth of the uneven part of this molded product (reference number 3 in FIG. 4) was measured with a vernier caliper. Next, a silicone resin was applied to one of the molds with the above uneven shape, and after leaving it in an atmosphere of 23 ° C for 24 hours to harden, the depth of the uneven shape made of the silicone resin was measured with a vernier caliper. The transfer rate was calculated by dividing the depth of the unevenness of the rectangular molded product by the depth of the unevenness of the silicone resin. A transfer rate of 0.9 or more was rated A, 0.7 or more but less than 0.9 was rated B, and less than 0.7 was rated C.

[0105] (Examples 1 to 12, Comparative Examples 1 to 12)

[0106] [Table 1]

[0107] [Table 2]

[0108] A comparison of Examples 1 to 12 and Comparative Examples 1 to 12 shows that by blending specific amounts of (B1) a nickel compound and (B2) a copper compound with (A) a thermoplastic resin having an electron-donating group, the thermoplastic resin has excellent thermal stability and mechanical properties.

[0109] Comparison between Example 2 and Comparative Example 8 shows that the complete decomposition temperature of the copper compound is 400° C. or higher, which results in excellent thermal stability and mechanical properties.

[0110] From Comparative Examples 11 and 12, it can be seen that in a thermoplastic resin not having an electron-donating group, even if a specific amount of the (B1) nickel compound and the (B2) copper compound are blended, the effect of improving thermal stability and mechanical properties cannot be obtained.

[0111] A comparison between Example 2 and Example 6 shows that the (B1) nickel compound and (B2) copper compound are better in thermal stability and mechanical properties when added as an aqueous solution than when added as a solid, which is believed to be because the (B1) nickel compound and (B2) copper compound are finely dispersed in the thermoplastic resin composition.

[0112] (Examples 13 to 16, Comparative Examples 13 and 14)

[0113] [Table 3]

[0114] Comparison between Example 13 and Comparative Example 13 reveals that by blending specific amounts of (B1) nickel compound and (B2) copper compound in the thermoplastic resin, excellent welding strength was achieved. This is believed to be because oxidation deterioration of the surface of the discontinuous fiber reinforced resin substrate was suppressed.

[0115] A comparison of Examples 14 to 16 with Comparative Example 14 reveals that by blending specific amounts of (B1) nickel compound and (B2) copper compound in a thermoplastic resin, excellent formability was achieved. This is believed to be because thickening due to oxidative degradation of the continuous fiber reinforced resin substrate could be suppressed.

[0116] (Examples 17 to 25, Comparative Examples 15 to 23)

[0117] [Table 4]

[0118] [Table 5]

[0119] A comparison of Examples 17 to 25 and Comparative Examples 15 to 23 shows that by blending specific amounts of (B1) nickel compound or (B2) copper compound and (C) amine compound with (A1) polyarylene sulfide, excellent thermal stability and mechanical properties are achieved.

[0120] (Examples 26 to 29, Comparative Examples 24 and 25)

[0121] [Table 6]

[0122] Comparison of Example 26 and Comparative Example 24 reveals that by blending specific amounts of (B1) nickel compound or (B2) copper compound and (C) amine compound with (A1) polyarylene sulfide, excellent welding strength is achieved. This is believed to be due to the suppression of oxidative deterioration of the surface of the discontinuous fiber reinforced resin substrate.

[0123] Comparison of Examples 27 to 29 with Comparative Examples 24 and 25 reveals that by blending specific amounts of (B1) nickel compound or (B2) copper compound and (C) amine compound with (A1) polyarylene sulfide, excellent shapability was achieved. This is believed to be because thickening due to oxidative deterioration of the continuous fiber reinforced base material could be suppressed. [Industrial Applicability]

[0124] The thermoplastic resin composition of the present invention can be molded by any method such as injection molding, compression molding, extrusion molding, etc., which are generally known. The thermoplastic resin composition of the present invention can be processed into various electric and electronic parts, automobile parts, aircraft parts, machine parts, etc., taking advantage of its excellent thermal stability and mechanical properties. In addition, the thermoplastic resin composition of the present invention can be used as fibers for clothing and industrial materials, and films for packaging and magnetic recording. Furthermore, by using it as a molded product in combination with a fibrous filler, it is expected to contribute to improving fuel efficiency and reducing greenhouse gas emissions by further reducing the weight, especially in automobile and aerospace applications. [Explanation of symbols]

[0125] 1: Hydrate desorption 2: Nitric acid elimination 3:Depth 4: On the mold 5: Under the mold 6: Laminate of continuous fiber reinforced substrate

Claims

1. A thermoplastic resin composition comprising (A) a thermoplastic resin having an electron-donating group and (B) a transition metal compound, wherein the electron-donating group is at least one of an ether group, a sulfide group, a thiol group, an amino group, and an alkylamino group, the (B) transition metal compound comprises (B1) a nickel compound and (B2) a copper compound, the (B2) copper compound having a complete decomposition temperature of 400°C or higher, and the thermoplastic resin composition has a nickel content of 0.001 part by mass or more and 4 parts by mass or less and a copper content of 0.001 part by mass or more and 4 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin having an electron-donating group (A).

2. A thermoplastic resin composition comprising (A) a thermoplastic resin having an electron-donating group, (B) a transition metal compound, and (C) an amine compound, wherein the electron-donating group is at least one of an ether group, a sulfide group, a thiol group, an amino group, and an alkylamino group, and wherein the thermoplastic resin composition has a melt viscosity retention of 90% or more and 7000% or less after heating for 30 minutes at a melting point of the thermoplastic resin having an electron-donating group + 70°C, wherein the thermoplastic resin having an electron-donating group (A) is composed of (A1) a polyarylene sulfide, and the (A1) polyarylene sulfide in the thermoplastic resin composition is a COOH group blocking rate represented by formula (I) of the polyarylene sulfide of 30% or more, (B) the transition metal compound includes (B1) a nickel compound or (B2) a copper compound, and the (B2) copper compound has a complete decomposition temperature of 400°C or more, and (C) the amine compound is a primary and / or secondary amine compound having a molecular weight of 5000 or less and a boiling point of 300°C or more, the transition metal content is 0.001 part by mass or more and 8 parts by mass or less, and the amine compound content is 0.01 part by mass or more and 5 parts by mass or less, per 100 parts by mass of the (A1) polyarylene sulfide. [0010] (In the formula, X represents the amount of carboxyl groups in the polyarylene sulfide (A1), and Y represents the amount of carboxyl groups in the polyarylene sulfide (A1) in the thermoplastic resin composition.)

3. The thermoplastic resin composition according to claim 1 or 2, wherein the copper compound (B2) is a copper halide.

4. The thermoplastic resin composition according to any one of claims 1 to 3, comprising 10 parts by mass or more and 400 parts by mass or less of the fibrous filler (D) per 100 parts by mass of the thermoplastic resin (A) having an electron donating group.

5. A fiber-reinforced resin substrate obtained by impregnating a continuous (D) fibrous filler or a reinforcing fiber substrate in which a discontinuous (D) fibrous filler is dispersed with the thermoplastic resin composition according to any one of claims 1 to 3.

6. A molded article obtained by molding the thermoplastic resin composition according to any one of claims 1 to 4 or the fiber reinforced resin substrate according to claim 5.

Citation Information

Patent Citations

  • Stabilized polyphenylene ether-polyamide composition

    JP1989163262A

  • Polyphenylene sulfide resin composition

    JP1994207102A

  • Heat-resistant polyarylene sulfide resin composition

    JP1994207103A

  • Organic electroluminescent element

    JP1996104867A

  • Preflux composition

    JP2009500842A